Strengthening green taxation within the framework of fulfilling the green deal conditions in the context of formation of the environmental security system of EU countries - Nikiforov, Petro; Abramova, Alla; Zhavoronok, Artur; Bak, Nataliia; Yaremchuk, Vitalii; Kulynych, Yurii (My University, 2024)
The study is dedicated to the scientific justification of the need to strengthen green taxation in the context of the Green Deal implementation and the greening of EU countries based on a comprehensive analysis of the effective functioning of the green taxation system, and presents the following vectors of its improvement. Scientific approaches to the interpretation of the essence of the economic value of green taxation, taking into account the systematicity of the economic, socio-political, innovative and infrastructural goals in the conditions of modern challenges, have been studied. Based on the international system of economic indicators, in particular the Environmental Policy Stringency Index, the actual state of green taxation in EU countries was assessed. By applying a methodological approach based on comparing the cost characteristics of regulation and stimulation of the ecologically oriented business activity of business entities with the cost characteristics of the tax burden and the regulatory nature of the impact due to the use of environmental taxation objects and damage to the environment, an assessment of the effectiveness of green taxation was carried out in 12 EU countries. The architecture of the environmental taxation environment of EU countries is presented, the interrelated elements of which are defined as the legal framework of green taxation, the toolkit for the Green Deal implementation with an emphasis on green taxation, as well as systemically important market transformations capable of influencing the economic and environmental behavior of business entities by using natural resources and pollution of the natural environment under the influence of time factors, globalization changes and subsequent future uncertainties. The author's approach to increasing the efficiency and improvement of green taxation, which is expedient to implement to achieve the Green Deal goals and the formation of the environmental security system of the European region, is substantiated.

Дослідження присвячене науковому обґрунтуванню необхідності посилення зеленого оподаткування в контексті імплементації Green Deal та екологізації країн ЄС на основі комплексного аналізу ефективного функціонування системи зеленого оподаткування та представлено такі вектори його вдосконалення. Досліджено наукові підходи до трактування сутності економічної цінності зеленого оподаткування з урахуванням системності економічних, соціально-політичних, інноваційних та інфраструктурних цілей в умовах сучасних викликів. На основі міжнародної системи економічних індикаторів, зокрема Environmental Policy Stringency Index, оцінено фактичний стан зеленого оподаткування в країнах ЄС. Застосувавши методологічний підхід, що ґрунтується на співставленні вартісних характеристик регулювання та стимулювання екологічно спрямованої підприємницької діяльності суб’єктів господарювання з вартісними характеристиками податкового навантаження та регуляторним характером впливу внаслідок використання об’єктів екологічного оподаткування та шкоди, завданої навколишнього середовища було проведено оцінку ефективності зеленого оподаткування у 12 країнах ЄС. Представлено архітектуру середовища екологічного оподаткування країн ЄС, взаємопов’язані елементи якої визначені як правова база зеленого оподаткування, інструментарій для реалізації Green Deal з акцентом на зелене оподаткування, а також системно важливі ринкові трансформації, здатні впливу на економічну та екологічну поведінку суб’єктів господарювання шляхом використання природних ресурсів та забруднення навколишнього природного середовища під впливом чинників часу, глобалізаційних змін та наступних невизначеностей майбутнього. Обґрунтовано авторський підхід до підвищення ефективності та вдосконалення зеленого оподаткування, який доцільно реалізувати для досягнення цілей Green Deal та формування системи екологічної безпеки європейського регіону
Keywords: environmental security; екологічна безпека; environmental taxation; екологічне оподаткування; environmental policy; екологічна політика; ecological growth; екологічне зростання; green taxation; зелене оподаткування; tax policy; податкова політика; tax administration; податкове адміністрування; Green Deal; регуляторні інструменти; regulatory instruments; поведінкові впливи; behavioral influences; глобалізація; globalization; ризики; risks; кафедра фінансів